Two Sympatric Spodoptera Species Could Mutually Recognize Sex Pheromone Components for Behavioral Isolation - Yan, Qi; Liu, Xiao-Long; Wang, Yu-Lei; Tang, Xiao-Qin; Shen, Zhi-Jie; Dong, Shuang-Lin; Deng, Jian-Yu (Frontiers in Physiology, 2019)
Spodoptera exigua and S. litura are two sympatric species in China and many other countries. Both moths employ a multiple component sex pheromone blend, including a common component Z9,E12-14:OAc, and two specific components Z9-14:OH and Z11-16:OAc for S. exigua, and one specific component Z9,E11-14:OAc for S. litura. For the two species, it has been well documented that males are able to recognize and behaviorally attracted by their species-specific sex pheromone, which functions as a means of reproductive isolation, but whether males could mutually recognize pheromone components of its sympatric species is unknown. In the present study, the electroantennogram (EAG) and field evaluation were conducted to address this topic. The EAG recordings revealed that males of each species could significantly respond to specific components of its sympatric species, although the response values were lower than that to its own major component. In field tests, the specific components Z9-14:OH and Z11-16:OAc of S. exigua strongly inhibited the male catches of S. litura to its conspecific sex pheromone, while specific component Z9,E11-14:OAc of S. litura significantly reduced the male catches of S. exigua to its sex pheromone. Furthermore, the combined lure of the two species completely inhibited male catches of S. litura, and significantly decreased the male catches of S. exigua, compared to the species-specific lure alone. The results demonstrated that males of the two sibling species could perceive the specific components of its counterpart, suggesting that mutual recognition of pheromone components may function to strengthen the behavioral isolation between the two species. Our study has added new knowledge to the reproductive isolation via sex pheromone communication system in sympatric moth species, and provided a base for designing of mating disruption tactics targeting multispecies by using insect sex pheromones.